(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to examine the influence of COSO 2004 Internal Control consisting of Control Environment, Risk Assessment, Control Activities, Information and Communication, and Monitoring of Non-Performing Loans. The type of research is explanatory study. The research population of Rural Banks (BPR) in Bandung is 51. Samples of 15 BPRs have a large enough number of borrowers and consistently make bad credit reports and are taken with a purposive judgment sampling technique. Data analysis uses multiple linear regression. Partial hypothesis test (t-test) and simultaneous test (F-test) using IBM SPSS 23.0. The results showed that Control Environment, Risk Assessment, Control Activities, Information and Communication, and Monitoring affect Non-Performing Loans partially or simultaneously.